Felicidad en la organización (2019)
Happiness is the most rewarding feeling a human being can feel, therefore this is the ultimate goal of life, to find what makes us happy, a place, a situation, a person; It is the goal of living. By understanding that working is the activity that most people spend the most time on, it is where people must focus to achieve the happiness they crave, this place is where a human being spends most hours in their life, here he meets people, resolves situations, and if it is handled well, it will be a vital part for the happiness of the people.